Excavating the archives: new perspectives on the Shanidar Cave Neanderthals - Emma Pomeroy; James Holman; Chris Hunt; Paul Bennett; Tim Reynolds; Lucy Farr; Lucía López-Polín; Jessica Twyman; Ross Lane; Graeme Barker (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In 1960, a remarkable cluster of bones from four Neanderthals (designated Shanidar 4, 6, 8 and 9) was recovered from Shanidar Cave, Iraqi Kurdistan. However, their delicate nature and removal en bloc meant that the relative positions of the skeletons and the chronology of their deposition were lost. Ralph Solecki, who led the excavations, described more remains left behind in the adjacent east wall of the trench. In 2018-2019 and 2022, Neanderthal remains (designated Shanidar Z and A respectively) were excavated from this east wall location directly adjacent to where the block was removed in 1960, and form part of the 1960 cluster. The recent availability of Solecki’s archives permits new insights into this unusual group of remains. While Shanidar 4’s skeleton was fully exposed in situ, the original position of Shanidar 6 is minimally published, and that of Shanidar 8 and 9 is unknown. Archival work suggests a different position for Shanidar 6 than that given in some previous publications, and that the remains may have been disturbed before Shanidar 4 was deposited above. Solecki’s unexcavated east wall bones correspond to Shanidar Z but not to Shanidar 6 (as Solecki initially assumed), given the position of Shanidar 6’s arm. How Shanidar 8 relates to the other skeletons remains unclear, but our archival work and new excavations point to the complex origin of this unique cluster of Neanderthal individuals, with implications for understanding Neanderthal mortuary/funerary behaviour.